Informalidad y heterogeneidad social: eficiencia y cooperación en comunidades y sociedades - Millán Valenzuela, Henio (Diálogos Latinoamericanos, 2019)
Informality is the way heterogeneous societies yield equilibriums between modern and pre-modern actors. These are expressed in a soft and negotiable institutionality that undermines the State’s capabilities to solve problems of social cohesion and welfare linked to modernity and free and competitive market. Nevertheless, informality and those equilibriums are needed to gestate and to manage order and governability, main concerns of power structures. Accordingly, these are forced to keep those equilibriums and to perpetuate informality and social heterogeneity.